2014
DOI: 10.1002/lary.24641
|View full text |Cite
|
Sign up to set email alerts
|

Physiology‐based minimum clinically important difference thresholds in adult laryngotracheal stenosis

Abstract: Flow-volume loops provide a quantitative method of objectively assessing outcomes in LTS. TPF is the most convenient index for this purpose, but AUCTotal /FVC provides marginally greater sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 25 publications
(38 reference statements)
3
48
1
Order By: Relevance
“…Pressure‐flow relationships can be measured with a pneumotachograph and a pressure catheter, or less invasively with spirometry . Pulmonary function variables, such as the expiratory disproportion index (ratio of the forced expiratory volume in 1 second to the peak expiratory flowrate), which are commonly used to diagnose lung pathologies including chronic obstructive pulmonary disease and asthma, have been shown to reliably diagnose adult laryngotracheal stenosis . Nouraei et al reported a strong correlation of pulmonary compliance (change in lung volume in response to unit change in driving pressure) with both anatomical stenosis severity and perceptual dyspnea severity .…”
Section: Discussionmentioning
confidence: 99%
“…Pressure‐flow relationships can be measured with a pneumotachograph and a pressure catheter, or less invasively with spirometry . Pulmonary function variables, such as the expiratory disproportion index (ratio of the forced expiratory volume in 1 second to the peak expiratory flowrate), which are commonly used to diagnose lung pathologies including chronic obstructive pulmonary disease and asthma, have been shown to reliably diagnose adult laryngotracheal stenosis . Nouraei et al reported a strong correlation of pulmonary compliance (change in lung volume in response to unit change in driving pressure) with both anatomical stenosis severity and perceptual dyspnea severity .…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has indicated that some of the metrics measured within PFTs may aide in differentiating LTS from other bronchopulmonary abnormalities 32 and may be useful in objectively assessing outcomes in LTS after airway surgery. 31,33 Further limitations include the sex distribution and sample size of our patient population. Future prospective studies would benefit from having more robust numbers that include more male patients to achieve an equal general distribution, data such as distance of stenosis from the glottis, length of stenosis, and percentage of stenosis to help stratify outcome differences between patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several measures, including peak inspiratory flow, peak expiratory flow, and areas under the curve, have been shown to be reliable predictors of disease severity for fixed extrathoracic lesions, as seen in idiopathic subglottic stenosis. 7,9 In the last two decades, a renewed interest has focused on using this data as an objective outcome measure in interventions for upper airway obstruction. 10 Most recently, these measures have been applied to subglottic stenosis to quantify surgical outcomes and disease severity in patients with ISGS.…”
Section: Introductionmentioning
confidence: 99%